I'm trying to do a proof by contradiction, but don't quite understand how to write it down formally or how to come to an answer in this case. I'm doing a conditional statement.
The problem I'm trying to solve is "Given the premises, h ^ ~r and (h^n) --> r, show that you can conclude ~n using proof by contradiction.
I've taken the negation of both h ^ ~r and (h^n) --> r, but I'm unsure how to use these two to prove ~n
so far I've written:
(i.)~((h^n) --> r)
therefore, ~n
The hardest part I'm having is that this isn't an actual statement that I can imagine a negation of, and a step by step answer of how to do one of these proofs would be really useful, thanks!
Suppose
~(((h ^ ~r) ^ ((h^n) --> r)) --> ~n)
Then,
~(~((h ^ ~r) ^ ((h^n) --> r)) v ~n)
=> ~(~(h ^ ~r) v ~((h^n) --> r)) v ~n)
=> ~((~h v r) v ~(~(h^n) v r)) v ~n)
=> ~((~h v r) v ((h^n) ^ ~r)) v ~n)
=> ~((~h v r) v (h ^ n ^ ~r)) v ~n)
=> ~((((~h v r v h) ^ (~h v r v n) ^ ((~h v r) v ~r)) v ~n)
=> ~(((true) ^ (~h v r v n) ^ (true)) v ~n)
=> ~((~h v r v n) v ~n)
=> ~(~h v r v n v ~n)
=> ~((~h v r) v (n v ~n))
=> ~((~h v r) v (true))
=> ~(true)
=> false //contradiction
Therefore,
((h ^ ~r) ^ ((h^n) --> r)) --> ~n